Apostasie - Margalit, Avishai (Mohr Siebeck, 2012)
Apostasy.
PublicationDate: 20210521
Keywords: Ethik -- Verrat -- liberale Gesellschaft -- menschliche Würde -- Frankfurter Allgemeine Ze -- Religionsphilosophie -- Anthropologie -- Ethics -- Array